Warraq’s War: A Critical Review (American Journal of Islam and Society, 2004)
Books Reviewed: Why I Am Not a Muslim. New York: Prometheus Books,2003; The Quest for the Historical Muhammad. New York: PrometheusBooks, 2000; What the Koran Really Says: Language, Text, andCommentary. New York: Prometheus Books, 2002; Leaving Islam:Apostates Speak Out. New York: Prometheus Books, 2003.Among other consequences of the horrific tragedy of 9/11 is the generationof a veritable cottage industry in books about Islam and Muslims.There had always existed a void regarding such books. In spite of itsAbrahamic roots and its long, if somewhat troubled, encounters with theWest, the significance of Arab countries in terms of western economicinterests and the steady growth of diasporic Muslims settling in the developedworld (easily surpassing the Jewish presence, probably even in theUnited States), Islam had remained a residual category entirely peripheralto American intellectual or cultural life.The unprecedented nature and the brutality of the event that led to theMuslim “explosion” into the public consciousness exposed the woefulindifference about Islam and reinforced the Orientalist stereotypes ofMuslims as mysterious, backward, and menacing. There was a predictableappetite among the public to know about Muslims, who had traditionallybeen pictured as quaint and dreadful “others” but were now increasinglybeing presented as angry and threatening “fanatics.” Some of the booksrushed to print were works of genuine scholarship, demonstrating experience,knowledge, and elegance. Others were obviously driven by commercial considerations rather than academic, and some were, indeed, shallow,trite, and often misleading.In the latter genre, two classes of books, both critical of Islam, quicklybecame popular: those written from an alarmist western perspective bysuch authors as Steven Emerson, Daniel Pipes, and Robert Spencer, andothers that were supposedly “insider” exposés and interrogations issuingfrom such critics as Irshad Manji, the brothers Irgun Mehmet and EmirFathi Caner, and Mohammad Mohaddessin. The doyen of the latter groupis, undoubtedly, Ibn Warraq ...